THE IMPACT OF TRAINING AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Ema Yudiani; Indra Rustiawan; Rabiyatul Jasiyah (Jurnal Ekonomi, 2023)
The purpose of this research is to determine the impact of training and work motivation on employee performance at the Perum Damri Bandung Branch Office. The Statistical Package for the Social Sciences (SPSS) program is used in this type of research. Data collection methods such as questionnaires and interviews. The sample consisted of 47 Perum Damri Bandung Branch Office employees. Validity tests, reliability tests, multiple linear regression analysis, and statistical tests are used. According to the findings of statistical tests, training and work motivation have a positive impact on the performance of employees at the Perum Damri Bandung Branch Office.